Mechanistic investigation of the Zn/Pd/C catalyzed cleavage and hydrodeoxygenation of lignin. Issue 8 (11th February 2016) - Klein, Ian; Marcum, Christopher; Kenttämaa, Hilkka; Abu-Omar, Mahdi M.
Abstract : While current biorefinery processes use lignin only for its heat value, the conversion of lignin to high value chemicals is an area of increasing interest. Abstract : While current biorefinery processes use lignin only for its heat value, the conversion of lignin to high value chemicals is an area of increasing interest. Herein we present a detailed mechanistic study of the hydrodeoxygenation (HDO) of lignin by using a synergistic Pd/C and Zn II catalyst through use of both lignin model compounds and lignocellulosic biomass. Spectroscopic data coupled with the study of lignin model compounds suggest that Zn II activates and facilitates removal of the hydroxyl group at the Cγ position of the β-O-4 ether linkage. Activation is proposed to occur through formation of a six-membered ring complex of Zn II coordinated to the oxygen atoms at Cα and Cγ of the lignin model compound guaiacylglycerol-β-guaiacyl.